2022
DOI: 10.3390/agriculture12122122
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and Inducible Expression of Genes Related to Salicylic Acid and Ethylene Pathways in a Moderately Resistant Tomato Cultivar Leads to Delayed Development of Meloidogyne javanica

Abstract: Knowledge of the molecular changes in resistant and susceptible cultivars during nematode attack is essential for developing plant resistance. Increased expression of genes related to the synthesis and signaling of salicylic acid, jasmonic acid, and ethylene is known to induce expression of genes related to defense against plant parasitic nematodes. Here, we inoculated approximately 3000 s-stage juveniles (J2s) of Meloidogyne javanica to moderately resistant and highly susceptible tomato cultivars (ALYSTE F-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…(2018). However, the findings of Asadi‐Sardari, Mahdikhani‐Moghadam, Zaki‐Aghl, and Vetukuri (2022) and Shekari‐Mahoonaki et al. (2022) partly contradict this, as they reported that resistant cultivars disrupted nematode penetration and delayed RKN development in tomato and pistachio, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(2018). However, the findings of Asadi‐Sardari, Mahdikhani‐Moghadam, Zaki‐Aghl, and Vetukuri (2022) and Shekari‐Mahoonaki et al. (2022) partly contradict this, as they reported that resistant cultivars disrupted nematode penetration and delayed RKN development in tomato and pistachio, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, post‐infection mechanisms involve initiating molecular and physiological processes within the plant that impede the creation of feeding sites. This subsequently retards the development of J2s and the reproductive progression of adult females (Asadi‐Sardari, Mahdikhani‐Moghadam, Zaki‐Aghl, & Vetukuri, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The defensive proteins that called pathogenesis-related proteins expressed by these genes in resistance or tolerance plant. Chemical induction of "systemic acquired resistance" is detected by using Benzothiadiazole in tomato and grapevines plants to suppress infection of M. incognita [79] and by using hydroxyurea in tomato to inhibit progress infection of M. javanica [80]. Also, chitosan stimulated production of defense-related chemicals in tomato plant and was associated through improvement process of resistance to root-knot nematode as well [81].…”
Section: Innovative Methodsmentioning
confidence: 99%